ALONE, LOST, AND UNPREPARED BY THE SYSTEM: INDIGENOUS CARE LEAVERS’ EXPERIENCES OF AGING OUT OF CHILD WELFARE CARE IN MANITOBA - Woodgate, Roberta L.; Bennett, Marlyn; Martin, Donna; Tennent, Pauline; Sandy, Clayton; Plaut, Shayna; Legras, Nicole; Bell, Ashley; Lys, Justin (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
Limited research has been carried out on Indigenous young people transitioning out of care in Canada. This article provides a coherent and meaningful account of the journey of aging out of care in the province of Manitoba, as presented by 17 Indigenous care leavers. Using a qualitative multilevel approach grounded in first-person narratives, this study focused on incorporating and elevating the voices of Indigenous care leavers. Participants detailed their experiences of planning for the transition and aging out of care, and described their life post-care. The care leavers expressed that the Child and Family Services-led process of planning for and transitioning out of care was unclear and failed to engage them as partners, and as a result left them ill-prepared for life post-care. Additionally, participants’ experiences serve as evidence of enduring gaps in transition supports, namely in mental health and interpersonal supports. These supports were often unavailable or inaccessible, challenges that were amplified during participants’ transition out of care and in the post-care period. The experiential knowledge from this study contributes valuable information to inform responsive child welfare transition policies and practices that are reflective of the experiences and needs of the population it intends to serve.